What Would Mrs. Astor Do? : The Essential Guide to the Manners and Mores of the Gilded Age - Tichi, Cecelia 1942-; Tichi, Cecelia 1942- (Book collections on Project MUSE., 2018)
"Cecilia Tichi invites us on a beautifully illustrated tour of the Gilded Age, transporting readers to New York at its most fashionable. A colorful tapestry of fun facts and true tales, What Would Mrs. Astor Do? presents a vivid portrait of this remarkable time of social metamorphosis, starring Caroline Astor, the ultimate gatekeeper" ...